(untitled) (Texas Journal of Medical Science, 2023)
Abstract of acute lung diseases. This problem is of particular importance when considering the growth of patients with diabetes. It should be noted that the emergence of antibiotics is a result of not using antibacterial drugs. Since the implementation. According to various authors, the number of complications in patients remains high, regardless of the rapid development of modern technologies used in the treatment of modern technologies requires the purchase of expensive specialized costs, the economic sector of the lung is also important for diabetes. In the background of appropriate surgical methods, use vacuum therapy in the treatment of acute diabetes and help early decontamination and cleaning of fibrin tissue and fibrin, accelerate the last necrotic tissue and fibrin This allows us to reduce the time of patients